Clinical practice guidelines for the antenatal management of dichorionic diamniotic twin pregnancies: a systematic review - Caroline O'Connor; Emily O'Connor; Sara Leitao; Shauna Barrett; Keelin O'Donoghue (BMC, 2023)
Abstract Objective This review aimed to identify guidelines with recommendations applicable to the antenatal management of dichorionic diamniotic twin pregnancies within high-income countries, appraise their methodological quality, and discuss the similarities and variability across guidelines. Method A systematic literature review of electronic databases was performed. Manual searches of guideline repositories and websites of professional organisations were performed to identify additional guidelines. The protocol for this systematic review was registered on PROSPERO (CRD42021248586, 25 June 2021). AGREE II and AGREE-REX tools were applied to assess the quality of eligible guidelines. A narrative and thematic synthesis described and compared the guidelines and their recommendations. Results Twenty-four guidelines were included, from which 483 recommendations were identified across 4 international organisations and 12 countries. Guidelines addressed eight themes and recommendations were classified accordingly: chorionicity and dating (103 recommendations), fetal growth (105 recommendations), termination of pregnancy (12 recommendations), fetal death (13 recommendations), fetal anomalies (65 recommendations), antenatal care (65 recommendations), preterm labour (56 recommendations) and birth (54 recommendations). Guidelines showed significant variability in recommendations, with conflicting recommendations regarding non-invasive preterm testing, definitions surrounding selective fetal growth restriction, screening for preterm labour and the timing of birth. Guidelines lacked a focus on standard antenatal management of DCDA twins, management of discordant fetal anomaly and single fetal demise. Conclusions Specific guidance for dichorionic diamniotic twins is overall indistinct and access to guidance regarding the antenatal management of these pregnancies is currently difficult. Management of discordant fetal anomaly or single fetal demise needs greater consideration.